Dual working parents’ awareness towards children internet activities in Federal Territory of Labuan - Wan Jaafar, Wan Munira; Faridzuan Teo, Ariff Azril; Hassan, Mohammad Mujaheed (Institut Sosial Malaysia, 2024)
This paper explores the awareness of dual-working parents towards their children's internet activities in Federal Territory of Labuan (F. T. Labuan), Malaysia. The internet has been considered as an important tool for people to exchange information and interact with each other. The existence of smartphones and mobile devices has become a menace towards parents to monitor their children’s internet activities. Moreover, with the huge shift of mothers participating in the work sector, it has been increasingly challenging for dual-working parents to check and control their children’s internet activities. A semi-structured interview was conducted with 11 families. The interview data were then analysed using qualitative method. The results showed that dual working parents in Labuan were mostly aware of the games and sites that their children often access dual working parents described that the main activities done by children are for the purpose of seeking entertainment, virtual social interaction and education.